Media Pembelajaran NodeMCU8266 Menggunakan IoT pada Mata Kuliah Sistem Kendali Berbasis Komputer di Prodi S1 Pendidikan Teknik Elektro Undiksha - Mohammad Jovi Ramadhan; Nyoman Santiyadnya; I Gede Made Surya Bumi Pracasitaram (Universitas Pendidikan Ganesha, 2022)
This study aims to create a NodeMCU8266 Learning Media using IoT in the Computer-Based Control System course at the Undiksha Electrical Engineering Education S1 Study Program. This research is classified as R&D (Research and Development) research. This study uses the statistical analysis method, the percentage is used to process data from content experts, media experts, and student trials. This study used a questionnaire as an instrument for collecting data from content experts, media experts, and students. The research results obtained: the results of the media expert test got a percentage of 94.79% with very decent qualifications, and the content expert validation test got a percentage of 93.75% with very decent qualifications. The score ranges for all 5 small group test respondents are listed in very high qualifications, and the score range for 20 large group test respondents are all listed in very high qualifications. NodeMCU8266 Learning Media Using IoT in the Computer-Based Control System Course in the Undiksha Electrical Engineering Education S1 Study Program is suitable for use in the learning process.